Hypertrophic Stenosis of the Pylorus – Single Center Experience - Vacić, Nikola; Kostić, Ana; Đorđević, Ivona; Bojović, Nikola; Milošević Anđelković, Žaklina; Jovanović, Andrijana (Medical Word, 2025)
This paper aims to show the challenges faced by clinicians when diagnosing hypertrophic pyloric stenosis, the distribution of patients according to gender and age, the variability of the ultrasound dimensions of the pylorus, and the frequency of postoperative complications. Retrospective analysis of electronic medical records, over three years, collected 22 patients with hypertrophic pyloric stenosis who underwent operative treatment - pyloromyotomy. Of 22 subjects, one child was female (4.55%) and 21 (95.45%) were male. The average age of patients of both sexes at admission was 31.2 ± 10.9 days. The youngest recorded case is a 9-day-old male newborn, and the oldest is a 60-day-old male infant. Complaints manifested themselves on average 5.3 ± 3.5 days before admission. On the ultrasound findings of the pylorus, the average length was 19.5 ± 2.3 mm, the average width was 13.4 ± 1.8 mm, and the average thickness of the muscle wall was 4.9 ± 0.6 mm. Postoperative complications were registered in two patients. One developed a fever of up to 40 degrees rectally on the first postoperative day. In the second case, it was a recurrence of hypertrophic pyloric stenosis, which required reintervention.Hypertrophic stenosis of the pylorus remains an enigma in the etiological sense. Usually healthy, full-term children with high Apgar scores become surgical patients soon after birth. Considering that it is one of the few diseases with adequate diagnostic and treatment methods, it is necessary to focus future research on finding the etiological factor that leads to it.